1998
DOI: 10.3181/00379727-217-44201
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cardioprotection by Estrogens

Abstract: Strong scientific evidence suggests that estrogen therapy offers considerable protection from coronary artery disease. While earlier studies focused mainly on favorable changes in plasma lipid profiles as the mechanism of estrogen action, recent studies have documented other mechanisms of action including direct effects on vascular wall. The other mechanisms include estrogen's role as an antioxidant, its ability to protect from DNA damage, inhibition of cell proliferation, and altering vascular response to vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 60 publications
0
40
0
3
Order By: Relevance
“…Epidemiological and case-controlled studies strongly suggest that postmenopausal women have about a 50% reduction in cardiovascular disease with estrogen administration (2,3). At least part of the cardiovascular benefits of estrogens are mediated through changes in lipoproteins (4,5), particularly by increases in high density lipoproteins (HDL); however, there is a strong feeling (6, 7) that as much as 50-75% of the beneficial effect of postmenopausal estrogen therapy is not explained by improvements in circulating lipid levels, but may involve other mechanisms including antioxidant protection (8). Recent studies have shown that a number of estrogens inhibit oxidation of low density lipoproteins (LDL) in vitro and protect against oxidative damage to DNA induced by hydrogen peroxide and arachidonic acid (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and case-controlled studies strongly suggest that postmenopausal women have about a 50% reduction in cardiovascular disease with estrogen administration (2,3). At least part of the cardiovascular benefits of estrogens are mediated through changes in lipoproteins (4,5), particularly by increases in high density lipoproteins (HDL); however, there is a strong feeling (6, 7) that as much as 50-75% of the beneficial effect of postmenopausal estrogen therapy is not explained by improvements in circulating lipid levels, but may involve other mechanisms including antioxidant protection (8). Recent studies have shown that a number of estrogens inhibit oxidation of low density lipoproteins (LDL) in vitro and protect against oxidative damage to DNA induced by hydrogen peroxide and arachidonic acid (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen therapy is well known to result in favourable changes in plasma lipid profiles (for a review see ref. 11 ). In the present study, total Figure 4 Liver (A), heart (B), and adrenal glands (C), weight (WT) relative to 100 g of body weight (BW) in sham-operated rats (SHAM), ovariectomized rats with placebo replacement (OVX), and OVX rats with estrogen replacement (OVXE2) studied under sedentary (SED; solid, grey, or open bars) or trained (TR; hatched and crosshatched bars) conditions.…”
Section: Physical Training and Estrogen Replacementmentioning
confidence: 99%
“…Estrogen therapy is well known to reduce food intake, body weight and fat deposition 2 -4 and to result in favourable changes in plasma lipid profiles. 11 Estrogens are also known to induce adenohypophyseal hypertrophy. 12,13 The sparse existing studies on the interaction of exercise training and estrogen replacement have been mainly aimed at the prevention of bone loss.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, estrogen therapy is well known to reduce body weight and fat deposition and result in favorable changes in plasma lipid profiles. [42][43][44] Estrogen has been reported as a beneficial factor in preventing cardiovascular diseases, like atherosclerosis, by keeping cholesterol levels low in premenopausal women. Menopausal women lose this protection because of a dramatic decrease in estrogen levels as a result of natural atrophy of the ovaries.…”
Section: Discussionmentioning
confidence: 99%